A Comparative Study between the ‎Mainstream, Critical, and Islamic ‎Approaches to Sustainable ‎Development - Rangga Tri Nugraha; Azza Bimantara (Journal of Comparative Study of Religions, 2022)
There are never-ending debates revolving around the concept of sustainable development as different groups of people have a different understanding of it. However, in a broader sense, it consists of three essential elements: conservation of the environment, intragenerational, and intergenerational justice. Currently, there are three broad groups of approaches to sustainable development: mainstream, critical, and Islamic approaches. It is best to assume that those three essential elements are inherent within each approach. The study aims to explain how those three approaches differ in establishing and maintaining the three elements of sustainable development by using a comparative analysis framework. Each element of sustainable development in each approach will be assessed based on the ability to produce relative decoupling, Rawlsian theory of justice, and whether they can help future generations meet their needs according to Maslow’s hierarchy of needs. The study shows that each approach has it's good and bad, looking at their practices. It can be said that the practices of the Islamic approach to sustainable development can fulfil the three elements the best and more easily among the three approaches compared. It is just that it does not have a clear set of specific guidance on how the Islamic view on the environment can be applied.